FAKTOR YANG BERPENGARUH TERHADAP KEPUASAN KONSUMEN DAN BEHAVIORAL INTENTION DENGAN PERCEIVED VALUE SEBAGAI VARIABEL MODERASI - Untung Sriwidodo, Ernawati & (Universitas Slamet Riyadi, 2012)
ABSTRACT It has often been argued that customer satisfaction can contri-bute significantly to a company’s success in a variety of ways. This study aims to analyze effect of three determinants of quality dimen-sions (product, service, and physical environment) to customer satisfaction. The model has been tested using surveyed data from 100 customers in Solo Wholesale Center. The data analyse use the multiple regression analysis and moderated regression analysis with standardized residual test. Finally, customer satisfaction is indeed a significant predictor of behavioral intention. This means that the more satisfied the consumers the more likely they are to repurchase product from the same retailer and more likely to do positive word-of-mouth communication. Thus, behavioral intentions expressed by consumers depend on their levels of satisfaction. Keywords: quality dimensions behavioral intentions, perceived value, customer satisfaction.